The correlation between exposure to cigarette smoke and the degree of mucosal epithelium-based dysplasia in Rattus norvegicus tongues - Dorisna Prijaryanti; Diah Savitri Ernawati; Desiana Radithia; Hening Tuti Hendarti; Rosnah Binti Zain (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Cigarette smoke contains various carcinogenic substances such as polycyclic aromatic hydrocarbons and nitrosamines. These chemicals not only have the potential to damage DNA, but can also induce genetic mutations and activate genes that function during apoptosis. Thus, if the gene is dysregulated, it will cause cells to survive, proliferate and subsequently lead to the development of cancerous ones. Histologically, the carcinogenic process affecting the oral cavity starts with hyperplasia and dysplasia, followed by severe dysplasia then leading to invasive cancer and metastatic processes in other bodies. Purpose: This study aims to reveal the correlation between exposure to cigarette smoke and the degree of epithelial dysplasia evident in research subjects. Methods: This study used 27 samples of Rattus norvegicus tongue, divided into three groups, namely; a control group, a treatment group subjected to four weeks’ exposure to cigarette smoke, and a treatment group subjected to exposure lasting eight weeks. Each rat was placed in an individual chamber and exposed to smoke from 20 cigarettes introduced by a pump via a pipe for 7.5 minutes. The degree of epithelial dysplasia in each case was subsequently observed microscopically using HE staining technique. Results: Mild epithelial dysplasia increased by 0.82%, during the fourth week of exposure to cigarette smoke and by 2.99% during the eighth week. Similarly, moderate epithelial dysplasia rose by 5.29% during the fourth week of exposure and 5.99% during the eighth week. Severe epithelial dysplasia also increased by 2.2% during the fourth week of exposure and by 2.66% during the eighth week. Conclusion: The longer the exposure to cigarette smoke, the higher the degree of ensuing dysplasia.